Cholesterol sensor SCAP contributes to sorafenib resistance by regulating autophagy in hepatocellular carcinoma - Danyang Li; Yingcheng Yao; Yuhan Rao; Xinyu Huang; Li Wei; Zhimei You; Guo Zheng; Xiaoli Hou; Yu Su; Zac Varghese; John F. Moorhead; Yaxi Chen; et al. (Journal of Experimental & Clinical Cancer Research, 2022)
Abstract Background Hepatocellular carcinoma (HCC) is one of the most malignant tumors and the fourth leading cause of cancer-related death worldwide. Sorafenib is currently acknowledged as a standard therapy for advanced HCC. However, acquired resistance substantially limits the clinical efficacy of sorafenib. Therefore, further investigations of the associated risk factors are highly warranted. Methods We analysed a group of 78 HCC patients who received sorafenib treatment after liver resection surgery. The expression of SCAP and its correlation with sorafenib resistance in HCC clinical samples were determined by immunohistochemical analyses. Overexpression and knockdown approaches in vitro were used to characterize the functional roles of SCAP in regulating sorafenib resistance. The effects of SCAP inhibition in HCC cell lines were analysed in proliferation, apoptosis, and colony formation assays. Autophagic regulation by SCAP was assessed by immunoblotting, immunofluorescence and immunoprecipitation assays. The combinatorial effect of a SCAP inhibitor and sorafenib was tested using nude mice. Results Hypercholesterolemia was associated with sorafenib resistance in HCC treatment. The degree of sorafenib resistance was correlated with the expression of the cholesterol sensor SCAP and consequent deposition of cholesterol. SCAP is overexpressed in HCC tissues and hepatocellular carcinoma cell lines with sorafenib resistance, while SCAP inhibition could improve sorafenib sensitivity in sorafenib-resistant HCC cells. Furthermore, we found that SCAP-mediated sorafenib resistance was related to decreased autophagy, which was connected to decreased AMPK activity. A clinically significant finding was that lycorine, a specific SCAP inhibitor, could reverse acquired resistance to sorafenib in vitro and in vivo. Conclusions SCAP contributes to sorafenib resistance through AMPK-mediated autophagic regulation. The combination of sorafenib and SCAP targeted therapy provides a novel personalized treatment to enhance sensitivity in sorafenib-resistant HCC.